Effects of Palm Kernel Expellers on Growth Performance, Nutrient Digestibility, and Blood Profiles of Weaned Pigs - J. Seo; W. Kim; J. Kim; J. K. Kim; S. C. Kim; Y. Jang; K. Jang; K. Kim; B. Kim; S. Park; I. Park; M. K. Kim; et al. (Asian-Australasian Journal of Animal Sciences, 2015)
This experiment was conducted to investigate the effects of palm kernel expellers on growth performance, nutrient digestibility, and blood profiles of weaned pigs. A total of 88 weaned pigs (6.94±0.76 kg body weight [BW]; 28 d old) were randomly allotted to 2 dietary treatments (4 pigs/pen; 11 replicates/treatment) in a randomized complete block design (sex as a block). The dietary treatments were a typical nursery diet based on corn and soybean meal (CON) and CON added with 20% of palm kernel expellers (PKE). Pigs were fed for 6 wk using a 3-phase feeding program with declining diet complexity and with phases of 1, 2, and 3 wk, respectively. Blood was collected from randomly selected 2 pigs in each pen before weaning and on d 7 after weaning. Pigs were fed respective dietary treatments containing 0.2% chromic oxide from d 29 to 35 after weaning. Fecal samples were collected from randomly selected 2 pigs in each pen daily for the last 3 days after the 4-d adjustment period. Measurements were growth performances, digestibility of dry matter, nitrogen and energy, white and red blood cell counts, packed cell volume, and incidence of diarrhea. The PKE increased average daily gain (ADG) (246 vs 215 g/d; p = 0.06) and average daily feed intake (ADFI) (470 vs 343 g/d; p<0.05) and decreased gain-to-feed ratio (G:F) (0.522 vs 0.628 g/g; p<0.05) during phase 2 compared with CON, but did not affect growth performance during phase 1 and 3. During overall experimental period, PKE increased ADG (383 vs 362 g/d; p = 0.05) and ADFI (549 vs 496 g/d; p<0.05) compared with CON, but did not affect G:F. However, no differences were found on digestibility of dry matter, nitrogen, and energy between CON and PKE. The PKE reduced frequency of diarrhea (15% vs 25%; p = 0.08) for the first 2 wk after weaning compared with CON. Similarly, PKE decreased white blood cells (8.19 vs 9.56×103/μL; p = 0.07), red blood cells (2.92 vs 3.25×106/μL; p = 0.09), and packed cell volume (11.1% vs 12.6%; p = 0.06) on d 7 after weaning compared with CON. In conclusion, addition of 20% palm kernel expellers to nursery diet based on corn and soybean meal had no negative effects on growth performance, nutrient digestibility, and blood profiles of weaned pigs.